2021
DOI: 10.30783/nevsosbilen.996191
|View full text |Cite
|
Sign up to set email alerts
|

Sosyal Bi̇lgi̇ler Öğreti̇mi̇nde Çözümlemeli̇ Öykünün Kullanimina Yöneli̇k Öğretmen Adaylarinin Görüşleri̇

Abstract: Sosyal bilgiler dersinde kullanılabilen edebi türlerden biri de çözümlemeli öyküdür. Herhangi bir konu ve kazanımı bilişsel, duyuşsal ve devinişsel yönleri ile öğrencilere öğretmeye yarayan çözümlemeli öykünün; düşünsel, ahlaki ve empatik olmak üzere üç boyutu bulunmaktadır. Derslerin tüm aşamalarında kullanılabilen çözümlemeli öykü aracılığıyla geçmişte yaşamış insanlar ve yaşanmış olaylar daha iyi anlaşılabilir, soyut bilgiler somutlaştırılabilir, gündelik yaşam dersin bir parçası haline getirilebilir. Öğren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In order to increase the effectiveness and permanence of the subject and to make the lesson attractive and more enjoyable while teaching historical subjects, literary products (poems) of the period discussed can be included. (Cantürk & Yeşiltaş, 2022;Kaymakcı et al, 2021). It has been observed that this approach is frequently applied in Iran textbooks.…”
Section: Recommendationsmentioning
confidence: 99%
“…In order to increase the effectiveness and permanence of the subject and to make the lesson attractive and more enjoyable while teaching historical subjects, literary products (poems) of the period discussed can be included. (Cantürk & Yeşiltaş, 2022;Kaymakcı et al, 2021). It has been observed that this approach is frequently applied in Iran textbooks.…”
Section: Recommendationsmentioning
confidence: 99%
“…There are studies on its use in the Social Studies course, its effect on success and attitude, its effect on environmental awareness, the opinions of teachers, students and teacher candidates, its effect on critical and empathetic thinking skills, and its use in value education (Akyürek Tay and Çakmak, 2020;Aydemir, 2010;Deveci, 2005). ; Deveci, 2007;Gedik, 2010;İbrahimoğlu and Öztürk, 2013;Kaymakçı, Turgut and Özalp, 2021;Selanik Ay and Konak, 2019;Uğur, 2007;Ünlüer and Yaşar, 2012). Studies have been found on its use in science classes, its effect on success, and its effect on concept learning, critical thinking and reading comprehension skills (Coştu, Ünal and Ayas, 2007;Horzum and Alper, 2006;Şahin and Çakmak, 2016).…”
Section: Introductionmentioning
confidence: 99%